Prefactibilidad para implementar una planta productora y exportadora de palta hass en el Distrito de Poroto, año 2021 - Esparza Sánchez, Claudia Abigail (2021)
The main objective of this project is to determine the commercial, technical, economic and financial feasibility for the implementation of a hass avocado producing and exporting plant for export to the United States market. It begins with the strategic planning that defines the bases and guidelines that will direct the current and future work of the plant, as well as the analysis of the external and internal environment that identifies the main opportunities of the organization and then design the project strategies. In the same way, the market study presents the analysis of the demand and supply of the potential market for the calculation of the satisfied demand that must be covered, being 438 tons of hass avocado during the first year. The technical study specifies the location and size of the plant, located in the District of Poroto (La Libertad), as well as the description of the production process, the requirements of inputs, labor and services, from the propagation of avocado to the packaging and labeling process. The total investment of the project amounts to US $ 991,492.35, of which 59.63% will be financed through a bank loan and 40.37% by own contributions. The economic and financial evaluation shows the financial viability of the project, obtaining a Net Economic Present Value of $ 545,393.55 and a Net Financial Present Value of $ 422,245.47, and a recovery value of 5.41 years and an Internal Rate of Financial Return of 29.71% being higher than the WACC which is 9.73%.